Sistem Pendukung Keputusan Pemilihan Virtual Private Server (VPS) Menggunakan Metode MOORA - Amanda, Vriska; Khairunnisa, Siti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Virtual Private Server (VPS) is a hosting solution where one physical server is divided into several isolated virtual servers. Each virtual server operates independently with the resources assigned to it. VPS uses virtualization technology that allows multiple virtual servers to run on one physical server. The main advantage of VPS is the ability to have complete control over the server without the need to manage complex physical infrastructure. In addition, VPS also offers a higher level of privacy and security compared to share hosting. However, in choosing a VPS, several problems can arise. Too few resources can hurt website or application performance, while too many resources can result in waste and unnecessary costs. Also, issues such as downtime, poor connection speed, or server constraints can cause disruption to the hosted website or application. To choose a VPS that suits user needs, the MOORA method is used as a decision support system. In this case, 9 VPS providers were selected which would be evaluated based on the criteria of CPU, RAM, Storage, Bandwidth and Cost. After applying the MOORA method, alternative A4 with a Yi value of 1,590 was declared the best alternative, and the Exabytes provider was considered the best VPS service provider.